Effects of Hyperbaric Oxygen Treatment on Gastrointestinal and Hepatic Inflammatory Response After Subarachnoid Hemorrhage: an Experimental Study - (:unkn) unknown (JOURNAL NEUROLOGICAL SCIENCES, 2017)
Objective (Background): To investigate whether experimental subarachnoid hemorrhage (SAH) could induce histopathologic changes and inflammatory response in the gastrointestinal system, and if this response may be attenuated by the potential effects of hyperbaric oxygen therapy (HBOT). Methods: Twenty rabbits were randomly divided into four groups. Group I was not subjected to SAH or sham operation. Group II were subjected to a sham operation. Group III were subjected to SAH and did not receive HBOT after SAH. Group IV were subjected to SAH and received five sessions of HBOT. Animals were euthanized through perfusion and fixation 72 h after the procedures. Four-millimeter tissue sections were obtained from the liver and terminal ileum and were examined microscopically. Arteriolar diameters were measured under light microscopy in five different examples taken randomly from each tissue. Statistical comparisons were performed using the Mann-Whitney U test. Results: Increased inflammation was seen in the liver and terminal ileum in the SAH group compared with the sham and control groups. Inflammation in the SAH group was high compared with the HBOT group, but it did not reach significance. There were no differences between groups regarding edema. Conclusions: We showed that HBOT performed after induced SAH was ineffective in the attenuation of inflammation in the liver and ileum tissues that occurred after SAH.
Keywords: Subaracnoid hemorrhage; hyperbaric oxygen therapy; inflammation; ileum; liver; ISCHEMIA-REPERFUSION INJURY; EXTRACEREBRAL ORGAN DYSFUNCTION; CEREBRAL VASOSPASM; LIVER-INJURY; RAT MODEL; THERAPY; BRAIN; APOPTOSIS; GUT; PROTECTS